2017
DOI: 10.1103/physrevlett.118.192003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Nonperturbative Corrections to the Chiral Separation Effect in Quenched Finite-Density QCD

Abstract: We demonstrate the nonrenormalization of the chiral separation effect (CSE) in quenched finite-density QCD in both confinement and deconfinement phases using a recently developed numerical method which allows us, for the first time, to address the transport properties of exactly chiral, dense lattice fermions. This finding suggests that CSE can be used to fix renormalization constants for axial current density. Explaining the suppression of the CSE which we observe for topologically nontrivial gauge field conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 82 publications
(105 reference statements)
3
17
0
Order By: Relevance
“…This is because then the limit N t → ∞ means the transition to continuum limit, and the appropriate tuning of the lattice spacing a allows to treat the final answer as the axial current at finite temperature T = 1/(N t a). However, for the interacting system the situation may be different, and at finite temperatures the corrections to the CSE current may appear [40] -the effect, which we do not discuss here.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…This is because then the limit N t → ∞ means the transition to continuum limit, and the appropriate tuning of the lattice spacing a allows to treat the final answer as the axial current at finite temperature T = 1/(N t a). However, for the interacting system the situation may be different, and at finite temperatures the corrections to the CSE current may appear [40] -the effect, which we do not discuss here.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…Firstly, the effect exists in thermodynamic equilibrium -the resulting current is nondissipative. Though the original derivation [1] employed subtractions of non-renormalized quantities, 2 analytical studies [2] in a well-regularized theory and numerical studies [3] confirmed the result.…”
Section: Introductionmentioning
confidence: 93%
“…The plots in Figure 3 clearly show that for the larger lattice volume the data for all topological sectors and chemical potentials we investigated are in perfect agreement with the free fermion result σ 0 CSE . A possible reason for the large finite size effects in topological sectors with non-zero Q is discussed in [32]. The results for all our simulations on larger lattices are summarised in Figure 2a. …”
Section: Resultsmentioning
confidence: 81%
“…In this contribution we report on a first-principles lattice study of the CSE, previously published in [32]. To avoid unquantifiable systematic errors we work with finite-density overlap fermions [33], which respect a lattice version of chiral symmetry, and use the properly defined conserved lattice axial vector current density [34,35]:…”
Section: Motivation and Introductionmentioning
confidence: 99%